Does Comorbid Posttraumatic Stress Disorder Affect the Severity and Course of Psychotic Major Depression? - Gaudiano, Brandon A. (2009)
BACKGROUND: Major depressive disorder (MDD) and posttraumatic stress disorder (PTSD) are commonly comorbid conditions that result in greater severity, chronicity, and impairment compared with either disorder alone. However, previous research has not systematically explored the potential effects of the psychotic subtyping of MDD and comorbid PTSD. METHOD: The sample consisted of psychiatric outpatients diagnosed with psychotic MDD with PTSD, psychotic MDD without PTSD, and nonpsychotic MDD with PTSD presenting for clinic intake. Clinical indices of severity, impairment, and history of illness were assessed by trained diagnosticians using the Structured Clinical Interview for DSM-IV supplemented by items from the Schedule for Affective Disorders and Schizophrenia. RESULTS: In terms of current severity and impairment, the psychotic MDD with PTSD and psychotic MDD only groups were similar to each other, and both tended to be more severe than the nonpsychotic MDD with PTSD group. In terms of history of illness, the psychotic MDD with PTSD group tended to show greater severity and impairment relative to either the psychotic MDD only or nonpsychotic MDD with PTSD groups. Furthermore, the psychotic MDD with PTSD patients had an earlier time to depression onset than patients with either psychotic MDD alone or nonpsychotic MDD with PTSD, which appeared to contribute to the poorer history of illness demonstrated in the former group. CONCLUSIONS: Future research should explore the possibility of a subtype of psychotic depression that is associated with PTSD, resulting in a poorer course of illness. The current findings highlight the need for pharmacological and psychotherapeutic approaches that can be better tailored to psychotic MDD patients with PTSD comorbidity.